Evolution and maintenance of sexual size dimorphism: aligning phylogenetic and experimental evidence - Kuntner, Matjaž; Elgar, Mark A. (Frontiers in Ecology and Evolution, 2014)
Integrating the insights derived from both phylogenetic and experimental approaches offers a more complete understanding of evolutionary patterns and processes, yet it is rarely a feature of investigations of the evolutionary significance of trait variation. We combine these approaches to reinterpret the patterns and processes in the evolution of female biased sexual size dimorphism in Nephilidae, a spider lineage characterized by the most extreme sexual size dimorphism among terrestrial animals. We use a molecular phylogeny to reconstruct the size evolution for each sex and reveal a case of “sexually dimorphic gigantism”: both sexes steadily outgrow their ancestral sizes, but the female and male slopes differ, and hence sexual size dimorphism steadily increases. A review of the experimental evidence reveals a predominant net selection for large size in both sexes, consistent with the phylogenetic pattern for females but not for males. Thus, while sexual size dimorphism in spiders most likely originates and is maintained by fecundity selection on females, it is unclear what selection pressures prevent males from becoming as large as females. This integrated approach highlights the dangers of inferring evolutionary significance from experimental studies that isolate the effects of single selection pressures.